Evaluation of growth, yield attributes, and yield of wheat varieties under Terminalia chebula trees - Akshay Kumar; Meenakshi Gupta; L. M. Gupta; Sarabdeep Kour; Punit Choudhary (Frontiers in Sustainable Food Systems)
Agroforestry plays a key role in the Indian economy in terms of tangible and intangible benefits. Agroforestry can simultaneously satisfy three important objectives, namely, protecting the ecosystems, producing a high-level output of economic goods, and increasing income and basic needs of the rural population, in addition to maintaining the resource base. In the Jammu subtropics, many fruit trees are grown with grasses or as the sole crop. There is not much awareness among farmers about the benefits of agroforestry. To overcome this, we conducted a field trial at the experimental farm of the Division of Agroforestry, Chatha, with the aim of exploring the possibility of growing different wheat varieties as an intercrop under the canopy of harad (Terminalia chebula Retz.) trees planted at a spacing of 5 × 4 m2. Three wheat varieties, namely, JAUW-598, WH-1080, and RSP-561, were grown under the Terminalia chebula trees, and growth and yield parameters were recorded at two distances from the base of the tree (0–1 m and 1–2 m). This study investigates the impact of distance from Terminalia chebula (harad) trees on the growth and yield of different wheat varieties in the agroclimatic conditions of Jammu and Kashmir. The primary objective was to determine the optimal spacing that minimizes competition for resources between the trees and crops, thereby enhancing wheat productivity. By evaluating key growth parameters and yield at varying distances from the tree base, this research aims to provide actionable insights for optimizing intercropping systems in the region. The growth and yield of varieties were significantly reduced under shade as compared to sole cropping. Maximum spike length (13.91 cm), tillers/plant (7.36), grains/spike (33.62), and grain yield (42.46 qha−1) were recorded in the variety RSP-561 grown in the open conditions. Overall, RSP-561 performed better among all the other varieties with a yield reduction of 47.83 and 12.15% at a distance of 0–1 m and 1–2 m, respectively, under shade as compared to the open conditions. All wheat varieties performed better at a distance of 1–2 m away from the tree base as the amount of shade/competition is less compared to a distance of 0–1 m from the tree base. The study concluded that wheat can be successfully grown at a distance of 1–2 m from the tree base to attain an additional income from the Terminalia chebula orchard.